The problems of Southeast Asian foreign students in U.P. in the school year 1961-1962 - Puakpong, Nontana 1936- ([Quezon City s.n.], 1962)
This study determines the academic and personal problems of a group of Southeast Asian foreign students enrolled in the University of the Philippines during the second semester of the school year 1961-1962.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Students, Foreign -- Philippines